Tradeoffs In Using Blockchain Technology For Security, Privacy, And Decentralization:theoretical And Empirical Perspectives (Informatica, 2023)
This paper is and extended abstract of the doctoral thesis. It identifies four selected topics in which blockchain technology can have a positive or transformative effect on existing solutions. We propose new protocols, which change the current standards to add functionality, improve performance or overcome limitations of existing blockchain networks. Specifically, we focus on container orchestration on the edge using a unique blockchain protocol for security, verifiability, and trust.